Utilizing an artificial intelligence system to build the digital structural proteome of reef-building corals. (18th November 2022) - Zhu, Yunchi; Liao, Xin; Han, Tingyu; Chen, J-Y; He, Chunpeng; Lu, Zuhong
Abstract: Background: Reef-building corals play an important role in the marine ecosystem, and analyzing their proteomes from a structural perspective will exert positive effects on exploring their biology. Here we integrated mass spectrometry with newly published ColabFold to obtain digital structural proteomes of dominant reef-building corals. Results: Of the 8, 382 homologous proteins in Acropora muricata, Montipora foliosa, and Pocillopora verrucosa identified, 8, 166 received predicted structures after about 4, 060 GPU hours of computation. The resulting dataset covers 83.6% of residues with a confident prediction, while 25.9% have very high confidence. Conclusions: Our work provides insight-worthy predictions for coral research, confirms the reliability of ColabFold in practice, and is expected to be a reference case in the impending high-throughput era of structural proteomics.